Prevalence and mechanism of triazole resistance in Aspergillus fumigatus in a referral chest hospital in Delhi, India and an update of the situation in Asia - Chowdhary, Anuradha; Sharma, Cheshta; Kathuria, Shallu; Hagen, Ferry; Meis, Jacques F. (Frontiers in Microbiology, 2015)
Aspergillus fumigatus causes varied clinical syndromes ranging from colonization to deep infections. The mainstay of therapy of Aspergillus diseases is triazoles but several studies globally highlighted variable prevalence of triazole resistance, which hampers the management of aspergillosis. We studied the prevalence of resistance in clinical A. fumigatus isolates during 4 years in a referral Chest Hospital in Delhi, India and reviewed the scenario in Asia and the Middle East. Aspergillus species (n=2117) were screened with selective plates for azole resistance. The isolates included 45.4% A. flavus, followed by 32.4% A. fumigatus, 15.6% Aspergillus species and 6.6% A. terreus. Azole resistance was found in only 12 (1.7%) A. fumigatus isolates.These triazole resistant A. fumigatus (TRAF) isolates were subjected to (a) calmodulin and β tubulin gene sequencing (b) in vitro antifungal susceptibility testing against triazoles using CLSI M38-A2 (c) sequencing of cyp51A gene and real-time PCR assay for detection of mutations and (d) microsatellite typing of the resistant isolates. TRAF harbored TR34/L98H mutation in 10 (83.3%) isolates with a pan-azole resistant phenotype. Among the remaining 2 TRAF isolates, one had G54E and the other had three non-synonymous point mutations. The majority of patients were diagnosed as invasive aspergillosis followed by allergic bronchopulmonary aspergillosis and chronic pulmonary aspergillosis. The Indian TR34/L98H isolates had a unique genotype and were distinct from the Chinese, Middle East and European TR34/L98H strains. This resistance mechanism has been linked to the use of fungicide azoles in agricultural practices in Europe as it has been mainly reported from azole naïve patients. Reports published from Asia demonstrate the same environmental resistance mechanism in A. fumigatus isolates from two highly populated countries in Asia i.e., China and India and also from the neighboring Middle East.